Computer program for the IBM personal computer which searches for approximate matches to short oligonucleotide sequences in long target DNA sequences. - Myers, E W (1986)
We describe a program which may be used to find approximate matches to a short predefined DNA sequence in a larger target DNA sequence. The program predicts the usefulness of specific DNA probes and sequencing primers and finds nearly identical sequences that might represent the same regulatory signal. The program is written in the C programming language and will run on virtually any computer system with a C compiler, such as the IBM/PC and other computers running under the MS/DOS and UNIX operating systems. The program has been integrated into an existing software package for the IBM personal computer (see article by Mount and Conrad, this volume). Some examples of its use are given.